Essential Amino Acids (EAA) Mixture Supplementation: Effects of an Acute Administration Protocol on Myoelectric Manifestations of Fatigue in the Biceps Brachii After Resistance Exercise - Negro, Massimo; Segreto, Valentina; Barbero, Marco; Cescon, Corrado; Castelli, Luca; Calanni, Luca; D’Antona, Giuseppe (Frontiers in Physiology, 2018)
Background: the purpose of this study was to investigate the acute effects of a single oral administration of an essential amino acids enriched mixture (EAA) on myoelectric descriptors of fatigue and maximal force production after a resistance exercise protocol (REP). Methods: twenty adult males (age: 27 ± 6 yrs; body mass: 72.7 ± 7.50 kg; height: 1.76 ± 0.06 m) were enrolled in a double-blind crossover placebo-controlled study. Subjects were randomized to receive EAA mix (0.15 g/kg BM) or a placebo (PLA) in two successive trials 7 days apart. In both trials subjects completed a REP two hours after the ingestion of the EAA mix or PLA. Before ingestion and after REP subjects performed isometric contractions of the dominant upper limb with the elbow joint at 120 degrees: 1) two maximal voluntary contractions (MVC) for 2-3 s; 2) at 20% MVC for 90 s; 3) at 60% MVC until exhaustion. Mean values of MVC, conduction velocity initial values (CV), fractal dimension initial values (FD), their rates of change (CV slopes, FD slopes) and the Time to perform the Task (TtT) were obtained from a multichannel surface electromyography (sEMG) recording technique. Basal blood lactate (BL) and BL after REP were measured. Results: Following REP a significant decrease of MVC was observed in PLA (P<0.05), while no statistical differences were found in EAA between pre-REP and post-REP. After REP, although a significant decrease in BL was found in both groups (P<0.0001) a higher BL Δ% was observed in PLA compared to EAA (P<0.05). After REP, at 60% MVC a significant increase of CV rate of change (P<0.05) was observed in PLA but not in EAA. At the same force level TtT was longer in EAA compared to PLA, with a significant TtT Δ% between groups (P<0.0001). Conclusion: acute EAA enriched mix administration may prevent the loss of force-generating capacity during MVC following a REP. During isometric contraction at 60% MVC after REP the EAA mix may maintain CV rate of change values with a delay in the TtT failure.